Dana Desa Mendorong Keberhasilan Pembangunan Ekonomi Lokal Desa di Indonesia - Dita Nurul Aini Mustika Dewi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
The decentralization policy is one of the central government's efforts to reduce monopoly power and distribute authority to local governments. In Indonesia, the decentralization policy is carried out to the village level through Law no. 6 of 2014 concerning Villages. The purpose of this study is to look at the role of village funds that have been disbursed by the government since 2015 in encouraging the success of local village economic development in Indonesia. This research was conducted with qualitative methods, namely literature review and exploratory. The results of this study indicate that the existence of a village fund stimulus policy is not the only funding for villages to develop local village economic resources. With village funds, the development of infrastructure supporting the village economy is carried out massively, while community empowerment cannot be carried out optimally so that it has not been able to reduce poverty levels optimally, but can reduce inequality levels slowly. Based on IDM data, there was an aggressive increase in the number of villages with advanced and independent status during the 2015-2020 period.